Biomarkers in Autism Spectrum Disorder: Challenges, Advances, and the Need for Biomarkers of Relevance to Public Health - Klin, Ami (Focus (Am Psychiatr Publ), 2018)
Although autism spectrum disorder (ASD) is the most strongly genetic of all complex neuropsychiatric disorders, it is still defined and diagnosed behaviorally. The vast genotypic and phenotypic heterogeneity of the condition necessitate a vigorous search for biological markers capable of aiding in diagnosis, identifying more homogeneous subgroups for biological study, individualizing treatment, and measuring treatment response. Many candidate biomarkers are available, spanning genetic, metabolic, electroencephalographic, magnetic resonance imaging, and neuropsychological methods. Although biomarker research has focused primarily on mechanistic etiologic hypotheses, the biomarkers more likely to result in optimized clinical outcomes in the near term are cost-effective and community-viable measures obtained through eye-tracking technology involving infants and toddlers. Although these tools are still far from being ready for widespread application, the goal is to develop objective procedures and measures for population-based screening and diagnosis to increase access to early treatment and intervention.